Peningkatan Intensitas Pencahayaan dan Distribusi Udara pada Ruang Kelas SMK Sasmita Jaya 2 - Aripin Triyanto; Marfin; Ojak Abdul Rozak (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The intensity of lighting and air distribution in a room is one of the important parameters of a healthy room. Currently, there are still many rooms that do not have a proper level of lighting intensity and air distribution, especially for teaching and learning activities. Currently SMK Sasmita Jaya 2 has one room for teaching and learning activities which is still far from feasible with the level of lighting intensity being at 45 lux with room temperature reaching 30.4 °C. This will have an impact on the comfort in teaching and learning activities in the room. For this reason, it is necessary to increase the intensity of lighting and reduce the temperature level of the room by repositioning lighting installation techniques and adding an indoor air distribution system. So that the lighting intensity of the SMK Sasmita Jaya 2 room can be increased and the room temperature can be lowered. The results of the measurement of lighting intensity after repositioning the lighting installation has increased to 105 lux from the previous 45 lux and the room temperature has decreased by 1.6 °C from the previous 30.4 °C to 28.8 °C after the addition of an air distribution system. From the results obtained, it can be concluded that Community Service activities in Increasing Lighting Intensity and Air Distribution in Classrooms of SMK Sasmita Jaya 2 were successfully carried out by increasing the intensity of lighting and decreasing room temperature.